Investigation on effect of fly ash volume percentage on microstructure and microhardness of aa7075âfly ash surface composites via fsp - Patil, N.A. (Springer Science and Business Media Deutschland GmbH, 2020)
In this study, friction stir processing (FSP) technique is used to fabricate aluminium AA7075 alloy reinforced with fly ash (FA) metal matrix composites (MMCs). The cheap and abundantly available industrial-waste fly ash (FA) micropowder is used as a reinforcing medium. The main focus of this study is to find out the optimal volume percentage that will bring out good mechanical properties on the selected base metal AA7075. The surface blind holes method is used for depositing the FA particles, and inter-cavity spacing is utilized as a parameter to control the volume percentage. For inter-cavity spacing of 4Â mm (S1), 6Â mm (S2), 8Â mm (S3), and 10Â mm (S4), the volume percentages of FA particles to be inserted are 2, 4, 6, and 8, respectively. After producing the MMCs, the microhardness and tensile tests have been conducted to study the mechanical properties of the MMCs. The microstructural analysis of Al 7075-FA MMCs has been conducted using field emission scanning electron microscopy (FESEM). The highest average microhardness value 178 HV and the highest UTS 240Â MPa are observed for the sample of S-2 combination. The microstructural observations confirm that breaking of FA microparticles and their more uniform distribution facilitates grain refinement which contributes to obtain enhanced microhardness and tensile strength. The FESEM-EDX and mapping confirm the presence of FA micropowder in the form of silicon oxide and other constituents. Â© Springer Nature Singapore Pte Ltd 2020.